National Sustainable Consumption and Production Strategies in the EU - Szlezak, Jozsef; Reichel, Almut; Reisinger, Hubert (Ökologisches Wirtschaften - Fachzeitschrift, 2008)
In the overall context of promoting sustainable development, sustainable consumption and production is an emerging field of targeted policy making at alllevels of governance, worldwide. In the European Union, governments have chosen different ways to implement this issue in the policy agenda.
Keywords: National Sustainable; Consumption; Production Strategies